MINERAL PHYSICS ANALYSIS OF ALLUVIAL ROCKS AS A SOURCE OF SHALLOW HYDROCARBON SEEPAGE IN BELIS VILLAGE, WARU BASIN, EASTERN SERAM ISLAND, MALUKU PROVINCE - Sapulete, Sisca M.; Nukuhaly, Manda S.; Souisa, Matheus (Indonesian Physical Review, 2024)
Belis Village is located in the Waru basin adjacent to the Bula basin on the eastern part of Seram Island and has potential shallow hydrocarbon manifestations. This research aims to determine the mineralogical characteristics of the rocks that make up shallow hydrocarbon manifestations at the research location. The research method used is physical analysis of minerals including petrographic analysis and XRD methods. The analysis results of the XRD method show an abundance of quartz minerals at 58%, followed by clay minerals at 35%, opaque minerals at 25%, and the rest in the form of cavities while feldspar minerals are secondary minerals. The results of the XRD analysis show that the more dominant mineral is protoenstatite (MgSio3) with an average abundance of 70.33% as a carrier of shallow hydrocarbon seeps, Quartz (SiO2) with an average abundance of 18.46%, and Clinoestatite with an average abundance of 11.21% as a mineral associated with shallow hydrocarbon seeps.